The Significance of Traditional Exegesis in Modern Quranic Sciences (Critical Analysis) - Sholihah, Ellyatus; Kahar, Abd. (International Conference on Islamic Studies, 2023)
For several centuries, traditional exegesis has played a crucial role in understanding the Quran within Islamic heritage. However, the significance of traditional exegesis has emerged as a profound debate in the era of modern Quranic research. The aim of this research is to conduct a critical analysis of the importance of traditional exegesis in the context of modern Quranic sciences. The research findings indicate that traditional exegesis holds historical and intellectual value that cannot be disregarded in comprehending the Quran. Nevertheless, it also faces a number of criticisms that need to be addressed in a contemporary context. This research discusses various efforts aimed at addressing these criticisms, including adaptation, reexamination, and integration with modern scholarly methodologies, highlighting the significant role of Muslim scholars and intellectuals in preserving the importance of traditional exegeses while remaining open to innovation and necessary changes to confront the challenges of the modern era.